Synergistic neurotoxicity of ciprofloxacin and nimesulide in unmasking a hidden catalyst for seizures: A case report - Gaikwad, Varsha Ratan; Gupta, Ashok Kumar; Dil, Subba; Jha, Ambika Nand (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Fluoroquinolones are widely prescribed broad-spectrum antibiotics with favourable pharmacokinetics but are associated with neurotoxicity in 1–2% of users. Reported manifestations include seizures, encephalopathy, psychosis, myoclonus, and dyskinesia. Ciprofloxacin, a commonly used agent, disrupts central nervous system homeostasis by inhibiting γ-aminobutyric acid-A (GABA-A) receptors and enhancing N-methyl-D-aspartate (NMDA) receptor activity, creating an excitatory milieu that heightens seizure risk, especially in predisposed individuals. Case description and management: A 54-year-old man with type 2 diabetes mellitus presented with diarrhoea, fever, and abdominal discomfort. He was empirically started on ciprofloxacin, nimesulide, and paracetamol; stool analysis later confirmed polymicrobial gastroenteritis. Two hours after his second ciprofloxacin dose, he developed a generalised tonic–clonic seizure (GTCS) despite no prior seizure history. Comprehensive metabolic, infectious, and neuroimaging evaluations were unremarkable. The Naranjo score was 7, indicating a probable adverse drug reaction. Ciprofloxacin was discontinued, and seizures were controlled with levetiracetam and lacosamide. His antimicrobial therapy was switched to amoxicillin–clavulanic acid, resulting in full neurological recovery and no further seizures. Conclusion: Ciprofloxacin-induced seizures likely stem from GABA inhibition and NMDA overactivation, potentiated by concomitant NSAID use. Prompt drug withdrawal and appropriate seizure management are essential. Prudent fluoroquinolone prescribing is critical to minimise CNS adverse effects and ensure patient safety.